Localization of Proteins to Different Layers and Regions of Bacillus subtilis Spore Coats - Imamura, Daisuke (American Society for Microbiology (ASM), 2010)
Bacterial spores are encased in a multilayered proteinaceous shell known as the coat. In Bacillus subtilis, over 50 proteins are involved in spore coat assembly but the locations of these proteins in the spore coat are poorly understood. Here, we describe methods to estimate the positions of protein fusions to fluorescent proteins in the spore coat by using fluorescence microscopy. Our investigation suggested that CotD, CotF, CotT, GerQ, YaaH, YeeK, YmaG, YsnD, and YxeE are present in the inner coat and that CotA, CotB, CotC, and YtxO reside in the outer coat. In addition, CotZ and CgeA appeared in the outermost layer of the spore coat and were more abundant at the mother cell proximal pole of the forespore, whereas CotA and CotC were more abundant at the mother cell distal pole of the forespore. These polar localizations were observed both in sporangia prior to the release of the forespore from the mother cell and in mature spores after release. Moreover, CotB was observed at the middle of the spore as a ring- or spiral-like structure. Formation of this structure required cotG expression. Thus, we conclude not only that the spore coat is a multilayered assembly but also that it exhibits uneven spatial distribution of particular proteins.